Representation of Sexual Identity Struggle in Aristotle and Dante Discover the Secrets of the Universe - Manarina Sabila, Putri; Supiastutik, Supiastutik; Purwita Wardani SWW, L. Dyah; Dyah Kusumayanti, Dina (JET ADI BUANA, 2022)
This paper discusses the journey of finding sexual identity in the novel Aristotle and Dante Discover the Secrets of the Universe. The analysis focuses on the effort of finding the sexual identity. The struggles before and after coming out are represented in the novel, as well as the critical position of the author. Stuart Hall's representation theory was used as a qualitative approach to analysis. The data of this study were obtained from words, phrases and sentences related to the phenomenon of gay and trans-gender in the selected novels. People are still uncomfortable with the behavior of the LGBT group, so it causes violence against groups associated with them. When the protagonist admits to being gay, he is abused and discriminated against by others, like in the novel. By relating the problem in the story to the author's biography and the struggle to establish his own sexual identity, the topic of sexual identity seems crucial to address as a part of this social phenomenon. This research was conducted as an initial research on the LGBT group, which is expected to be useful for future research.